2011
DOI: 10.1002/app.34151
|View full text |Cite
|
Sign up to set email alerts
|

Thermal properties of polyurethane binder with 2‐(ferrocenylpropyl)dimethylsilane‐grafted hydroxyl‐terminated polybutadiene

Abstract: We synthesized a ferrocene-based burning rate catalyst, 2-(ferrocenylpropyl) dimethylsilane (FPDS). FPDS-grafted hydroxyl-terminated polybutadiene (FPDS-g-HTPB) was synthesized using hydrosilylation with a Pt catalyst. The structures of FPDS and FPDS-g-HTPB were investigated by Fourier transform infrared spectroscopy and nuclear magnetic resonance. HTPB-based polyurethanes were prepared from HTPB, ,6-hexamethylenediisocyanate (HDI), and HDI-trimer. Polyurethane network was prepared with an (NCO)/(OH) ratio of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 17 publications
1
27
0
1
Order By: Relevance
“…Available polymer matrices include polymer binders used in composite solid propellants and some reactive polyesters or polyurethanes. Especially, ferrocene‐modified polymer binders such as hydroxyl‐terminated polybutadiene (HTPB) can be a kind of difunctional (binder and BR catalyst) substance, which have attracted considerable attention in recent years …”
Section: Synthesis Of Ferrocene‐containing Polymers and Derivatives Umentioning
confidence: 99%
See 1 more Smart Citation
“…Available polymer matrices include polymer binders used in composite solid propellants and some reactive polyesters or polyurethanes. Especially, ferrocene‐modified polymer binders such as hydroxyl‐terminated polybutadiene (HTPB) can be a kind of difunctional (binder and BR catalyst) substance, which have attracted considerable attention in recent years …”
Section: Synthesis Of Ferrocene‐containing Polymers and Derivatives Umentioning
confidence: 99%
“…Researchers have explored some other compounds similar to butacene. Meanwhile, other methods of modification of HTPB were also developed …”
Section: Synthesis Of Ferrocene‐containing Polymers and Derivatives Umentioning
confidence: 99%
“…However, the weak polarity of main chain of HTPB leads to poor compatibility with other polar components, and limits its applications. 12,43 DMA analyses were performed to evaluate the dynamic mechanical properties of both elastomers. The physical properties of triblock copolymer can satisfactorily meet the processing requirements for a thermoset polymer according to the study results.…”
Section: Dynamic and Static Mechanical Properties Of Triblock Copolymmentioning
confidence: 99%
“…3 Ferrocene derivatives are also known as high-burning-rate catalysts for composite propellants containing oxidizer AP and aluminum powder, 4-6 but they have some drawbacks, such as their migration to insulation composition during storage, evaporation, or sublimation loss during processing, and phase separation by crystallization. 9 Some later studies indicated that linking ferrocenes to the propellant binder via graing or introducing ferrocenes into the binder backbone during curing [10][11][12] or graing ferrocene on the hyper-branched structures 13 are effective ways to augment burning rates and to reduce the migration tendency. 9 Some later studies indicated that linking ferrocenes to the propellant binder via graing or introducing ferrocenes into the binder backbone during curing [10][11][12] or graing ferrocene on the hyper-branched structures 13 are effective ways to augment burning rates and to reduce the migration tendency.…”
Section: Introductionmentioning
confidence: 99%